2019
DOI: 10.1016/j.jpedsurg.2019.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of imaging modalities for preoperative assessment of anorectal malformation in the pediatric population

Abstract: Objective: The aim of this study was to compare the accuracy of MRI, colostography/fistulography, and X-ray imaging modalities for preoperative diagnosis of anorectal malformations (ARMs) in pediatric patients. Methods: This retrospective analysis included a total of 84 pediatric patients with ARMs. Preoperative imaging findings were assessed by 2 radiologists and compared to surgical findings. Results: MRI identified anomalies of the spine in 25 of 84 patients (29.8%), anomalies of the genital system in 7 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The use of magnetic resonance imaging (MRI) for the preoperative assessment of patients with anorectal malformations (ARM) has increased in recent years [1] . In children with ARM, MRI provides detailed one-stop-shop information regarding the type of malformation, condition of the sphincter-complex, gynecological comorbidities, urological anomalies, presence of presacral masses, and caudal regression syndrome [2] .…”
Section: Introductionmentioning
confidence: 99%
“…The use of magnetic resonance imaging (MRI) for the preoperative assessment of patients with anorectal malformations (ARM) has increased in recent years [1] . In children with ARM, MRI provides detailed one-stop-shop information regarding the type of malformation, condition of the sphincter-complex, gynecological comorbidities, urological anomalies, presence of presacral masses, and caudal regression syndrome [2] .…”
Section: Introductionmentioning
confidence: 99%
“…4 However, MRI can further depict other minor associated anomalies, as well as help to decide the surgical approach, as it permits evaluation of penile structures; in fact, comprehensive studies comparing MRI to other imaging techniques have already demonstrated its superiority, yielding greater accuracy. 14,15 Also, to determine which penis has the full functional capacity, the presence of two corpus cavernosum and one corpus spongiosum is decisive, as well as spermatic cords, as MRI demonstrated in our patient; such structures will determine which penis will be excised. In more complex cases, where there is only one corpus cavernosum in each penis, the joining of two corporal bodies with penile reconstruction has been reported.…”
Section: Discussionmentioning
confidence: 81%
“…More recent literature has moved away from the modified approach with promotion of a standard feed and sleep (“feed and wrap”) pelvic MRI without distending the distal colon loop or injecting into the perineal fistulas [ 6 , 14 ]. With either approach, MRI is advocated as a promising one-stop-shop modality, allowing assessment of not only the whole pelvic contents (particularly in females) and fistulas but also confidently excluding presacral masses, evaluating the spine, evaluating the perineal sphincter muscle complex (at least in older patients) and evaluating the renal tracts, in one sitting [ 8 , 17 20 ]. In two recent publications, conventional high-resolution pelvic MRI is reported to have a higher sensitivity at appropriately detecting the anatomy of the rectal pouch (above versus at versus below the pelvic floor) when compared to the traditional distal colostogram (the recognised gold standard being the surgical findings).…”
Section: Postnatal Imagingmentioning
confidence: 99%